2011
DOI: 10.1111/j.1467-789x.2010.00774.x
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for the prevention of overweight and obesity in preschool children: a systematic review of randomized controlled trials

Abstract: SummaryThe objective of this study was to analyse interventions for the prevention of overweight and obesity in children under 5 years of age. We carried out a systematic review focusing exclusively on randomized controlled trials (RCTs). Data sources include Medline, Cochrane Library, EMBASE, CINHAL, PsychInfo and Web of Science. Data were extracted from seventeen articles describing seven RCTs identified through electronic search, screening of references in systematic reviews, own files and contact with auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
90
0
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 37 publications
7
90
0
13
Order By: Relevance
“…Accordingly, short-term in-patient interventions over 2-8 weeks are very unlikely to offer long-term success (20,(45)(46)(47) . The successful interventions required periods of 6-12 months (26,41,42) . However, there are no studies analysing the relationship between the duration of interventions and long-term outcomes.…”
Section: Duration Of Interventionmentioning
confidence: 99%
“…Accordingly, short-term in-patient interventions over 2-8 weeks are very unlikely to offer long-term success (20,(45)(46)(47) . The successful interventions required periods of 6-12 months (26,41,42) . However, there are no studies analysing the relationship between the duration of interventions and long-term outcomes.…”
Section: Duration Of Interventionmentioning
confidence: 99%
“…32 Other trials assessing children in preschoolenvironmentsfailedtodemonstrate improvements in growth patterns. 9,33 We suspect that the success of our trial was attributable to the inclusion of parent-child dyads instead of preschoolaged children alone. Similarly, a recently published small trial by Stark et al 34 of 17 families with obese preschool-aged children reported reductions in BMI after an in-home family-centered intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Of 7 published randomized controlled trials with this age group, most were school based. 9 In their review of these studies, Monasta et al 9 concluded that none of the interventions altered weight gain or BMI. Reasons suggested for the failure of these interventions included faulty study designs, inadequate parental engagement, or failure to account for macro-environments (eg, neighborhoods, community, society).…”
mentioning
confidence: 99%
“…However, all RCTs have focused on obese children so far and even less is known about intervention effects in overweight children (Monasta et al 2010;Oude et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Guidelines recommend long-term outpatient training programs consisting of a combination of physical exercise, nutrition education, and behaviour counselling for obese children and adolescents, but only few programs have run and have been evaluated in the past (Oude et al 2009;Monasta et al 2010). A recent Cochrane review (Oude et al 2009) concerning treatment in already obese children including 64 randomized controlled trials (RCTs) with 5,230 participants identified lifestyle interventions for obese children focused on physical activity and sedentary behavior in 12 studies, diet in 6 studies, and 36 concentrated on behaviorally orientated treatment programs.…”
Section: Introductionmentioning
confidence: 99%